Profil Kemandirian Belajar Siswa Dan Implikasinya Bagi Program Bimbingan Belajar - Haerani, Irma; Khairun, Deasy Yunika; Conia, Putri Dian Dia (Konseling Edukasi : Journal of Guidance and Counseling, 2020)
Profile Of Independence Learning Students And Their Implications For The Program Of Learning Guidance. This study aims to find a picture of the learning independence of class IX students in the 2019/2020 school year at SMPN 3 Serang City. The research method used in this study is a descriptive method with a quantitative approach. The research subjects were 159 students of class IX in the 2019/2020 school year that were randomly selected. The instrument used was a student learning independence questionnaire. The results showed the level of learning independence of class IX students in the 2019/2020 school year at SMPN 3 Serang City in the low category with a percentage of 17.61% by 28 students, the medium category with a percentage of 64.78% by 103 students, a high category with a percentage of 17.61% by 28 students . After knowing the picture of students' learning independence, a study guidance program is arranged based on the results of the research obtained. The tutoring program is expected to be able to help students to overcome the learning difficulties they face, and to develop effective ways of learning, so that students' learning independence can be improved. Keywords: Learning Independence, Program of Learning Guidance